Identifikasi Keanekaragaman Tumbuhan Lumut (Bryophyta) Di Kawasan Universitas Negeri Medan - Beatrix Octaviana Silitonga; Jennya Theresia Br Tarigan; Joevina Emmiya Br Ginting; Nisa Holida Siagian; Orissa Paskah Syaloom N; Ruth Cessaminar Gultom (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Moss plants (Bryophyta) are bioindicators of environmental pollution. Identification of moss plant diversity has never been carried out at Medan State University. The research design used to obtain field data is by using the exploratory method. Sampling was purposive sampling in the humid environment around Medan State University, especially in parts that have lots of trees. The results obtained in this study show that there are two types of moss plants, namely leaf moss and liverworts. There are three species of leaf moss found, namely, Sphagnum moss, Entondon seductrix, Andreaea rupestris while the liver moss found is the Bozzania trilobata species.